Empowering Housewives Through the Processing of Spice Plants into Innovative Body Care Products at Denai Kuala Pantai Labu Deli Serdang: Pemberdayaan Ibu Rumah Tangga Melalui Pengelolaan Tanaman Rempah Menjadi Produk Perawatan Tubuh Inovatif di Denai Kuala Pantai Labu Deli Serdang - Putri Zira Angraini; Wilda Nalfira; Rosramadhana Rosramadhana; Sudirman Sudirman; Zulaini Zulaini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Denai Kuala Village has excellent potential in the fisheries, tourism, and agriculture fields. This village also has the potential of spice plants that have been developed through the Rumah Nusa (Family Nutrition) Program. The potential of Denai Kuala Village has not been optimally utilized, especially for agricultural and plantation products. The community has a low level of education and economy. A community service program is planned to provide alternative solutions to the problems of Denai Kuala Village, especially to empower housewives. The program is aimed at revitalizing home industries through the management of spice plants and developing products from these spices to increase family income. This effort is carried out as an effort to inherit and improve the economy through empowering women in continuing development equality that upholds the dignity of a just nation. The implementation of activities is carried out through four main stages, namely planning, organization, actualization, and supervision. Implementation steps include: (1) surveys and analysis of target groups through field visits to collect data on activities to be implemented; (2) identifying program needs through refining predetermined ideas; (3) building infrastructure and facilities; (4) realizing the concept through outreach activities and making body care products for housewives as the target group in the implementation; (5) Evaluation. The results of the activities show the achievement of the initial objectives of the program, where the housewife partners have increased their knowledge in terms of managing and utilizing spice plants as body care products, to marketing techniques on the e-commerce platform.